Reciprocal effects of alpha-synuclein aggregation and lysosomal homeostasis in synucleinopathy models - Alice Drobny; Fanni Annamária Boros; Denise Balta; Susy Prieto Huarcaya; Deniz Caylioglu; Niyeti Qazi; Julia Vandrey; Yanni Schneider; Jan Philipp Dobert; Caleb Pitcairn; Joseph Robert Mazzulli; Friederike Zunke (Translational Neurodegeneration, 2023)
Abstract Background Lysosomal dysfunction has been implicated in a number of neurodegenerative diseases such as Parkinson’s disease (PD). Various molecular, clinical and genetic studies have highlighted a central role of lysosomal pathways and proteins in the pathogenesis of PD. Within PD pathology the synaptic protein alpha-synuclein (αSyn) converts from a soluble monomer to oligomeric structures and insoluble amyloid fibrils. The aim of this study was to unravel the effect of αSyn aggregates on lysosomal turnover, particularly focusing on lysosomal homeostasis and cathepsins. Since these enzymes have been shown to be directly involved in the lysosomal degradation of αSyn, impairment of their enzymatic capacity has extensive consequences. Methods We used patient-derived induced pluripotent stem cells and a transgenic mouse model of PD to examine the effect of intracellular αSyn conformers on cell homeostasis and lysosomal function in dopaminergic (DA) neurons by biochemical analyses. Results We found impaired lysosomal trafficking of cathepsins in patient-derived DA neurons and mouse models with αSyn aggregation, resulting in reduced proteolytic activity of cathepsins in the lysosome. Using a farnesyltransferase inhibitor, which boosts hydrolase transport via activation of the SNARE protein ykt6, we enhanced the maturation and proteolytic activity of cathepsins and thereby decreased αSyn protein levels. Conclusions Our findings demonstrate a strong interplay between αSyn aggregation pathways and function of lysosomal cathepsins. It appears that αSyn directly interferes with the enzymatic function of cathepsins, which might lead to a vicious cycle of impaired αSyn degradation. Graphical abstract Lysosomal trafficking of cathepsin D (CTSD), CTSL and CTSB is disrupted when alpha-synuclein (αSyn) is aggregated. This results in a decreased proteolytic activity of cathepsins, which directly mediate αSyn clearance. Boosting the transport of the cathepsins to the lysosome increases their activity and thus contributes to efficient αSyn degradation.